Stress management to improve academic self-efficacy among undergraduate students : A Scoping Review - Septiansyah, Dhimas Anggi; Windarwati, Heni Dwi; Hariyanti, Tita; Lestari, Retno (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background : Undergraduate students face various academic challenges that often lead to significant stress. A lack of robust academic self-efficacy contributes to various mental health issues among undergraduate students, emphasizing the need for effective stress management strategies. The absence of protocols and systematic reviews registered in the International Prospective Register of Systematic Reviews (PROSPERO) focusing on stress management for improving undergraduate students' academic self-efficacy highlights the lack of comprehensive research on this topic. Objectives : This study aims to conduct a scoping review on stress management to improve academic self-efficacy among undergraduate students. Methods : This literature review used PICO framework to develop articles questions (P : undergraduate students,  I : stress management, C:  not  applicable,  and  O: academic self-efficacy). Articles search for literature review was conducted during November and December 2024. This  study  used  ProQuest, ScienceDirect and Pubmed databases. The keywords that used in this scoping review for the ProQuest were "stress management" AND "self-efficacy" AND "college student". For the ScienceDirect, the keywords were "non-pharmacological intervention" AND "self-efficacy" AND "college students". For the PubMed, the keywords used were "intervention" AND "self-efficacy" AND "college student".Results : A total of 6,539 articles were retrieved from ProQuest, ScienceDirect, and PubMed databases. After applying eligibility criteria, 19 articles were included in the review. The findings identified five cognitive, affective, and behavioral-based stress management interventions, three physical activity-based interventions, four information and communication technology-based interventions, and seven curriculum-based interventions. Conclusions : A comprehensive approach to stress management can significantly improve academic self-efficacy among undergraduate students. It is crucial for healthcare professionals, particularly nurses and educators, to integrate stress management techniques to improve academic self-efficacy among undergraduate students.